STUDENT REFLECTIONS ON A GENERAL ENGLISH READING AND WRITING MODULE: A QUALITATIVE STUDY OF NON-ENGLISH MAJOR AT POLITEKNIK NEGERI SRIWIJAYA - Wirda Ningsih; Sunani; Genta Ulina Hutagalung; Iwan Setiadi; Ajeng Ayutia Irdianti; Siswanda Trialoka (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2025)
This study explores non-English major vocational students’ reflections on a General English module for reading and writing. Employing a qualitative descriptive design, data were collected through semi-structured interviews with 20 second-semester tourism students at Politeknik Negeri Sriwijaya whose English proficiency ranged from A2 to B1 (CEFR). The module integrated real-world vocational themes, scaffolded writing tasks, grammar support, and pre-reading activities to address persistent challenges in reading comprehension and written expression. The data were analyzed using thematic analysis following Braun and Clarke’s six-phase framework. The findings indicate that the module enhanced students’ confidence and engagement in reading and writing through thematic relevance and structured learning support. Brainstorming and pre-reading activities were perceived as particularly effective in activating prior knowledge and facilitating idea organization. However, challenges related to grammar retention and vocabulary load remained, especially for lower-proficiency learners. The study highlights the pedagogical value of contextualized and learner-centered General English modules in vocational settings and suggests the need for differentiated support and enhanced vocabulary scaffolding. These findings contribute to the design of responsive English instruction for non-English majors in vocational education.